Is there still room for therapeutic drug monitoring of linezolid in patients with tuberculosis?. Issue 4 (April 2016) - Bolhuis, Mathieu S.; Tiberi, Simon; Sotgiu, Giovanni; De Lorenzo, Saverio; Kosterink, Jos G.; van der Werf, Tjip S.; Migliori, Giovanni Battista; Alffenaar, Jan-Willem
We read with great interest the comments from D. Cattaneo and co-workers on our article describing a retrospective study in multidrug-resistant tuberculosis (MDR-TB) patients receiving linezolid tailored to the individual patient using therapeutic drug monitoring as part of their regular treatment [1]. Cattaneo and co-workers correctly summarise that one of our findings was that we did not observe any significant differences between exposure to linezolid and adverse events. Indeed, this observation may be surprising with a toxic drug like linezolid, but it is not a reason to rule out therapeutic drug monitoring as a tool for optimising the treatment regimens of TB patients. The explanation for this lies in the design of our study, the characteristics of the patient population, and the specific dosing regimen used for MDR-TB patients. A retrospective study demonstrates the clinical complexity of MDR-TB patient management: TDM of linezolid is useful http://ow.ly/Xm2EA